Study the Rate and Causes of the Screening Test of the Cervix Cancer Among Women in Ardabil City - roya Motavalli; Tavakkol Mousazadeh; Amir Mousazadeh; Ayda Fallah Asadi (Asian Pacific Journal of Environment and Cancer, 2018)
Cervix cancer is one of the most common cancers in women, particularly in developing countries and Asian countries that many science centers around the world consider the pap smear screening test as the best solution for the control of cervical cancer. Several studies have shown that to tend women for doing a pap smear is regularly decreasing, and about one-fifth of women have not had a pap smear. This study was done to investigate rate and causes of the cervix cancer screening test among women Ardabil. In this cross-sectional study, 300 women referred to health centers in Ardabil were selected by multistage sampling. Data were collected through a researcher made questionnaire. For data analysis, SPSS Software version 18 and descriptive and inferential statistics were used. The rate of cervical cancer screening test in this study was 48%. The role of knowledge as personal factors of pap smear screening test was significant statistically (p<0.05). Among the risk factors for cervical cancer, there was observed significant relationship between uterine diseases history and number of pregnancies and pap smear test (p<0.05). Of family and social factors on women's education and employment, occupation and level of education was no significant relationship with using pap smear test. However, there was a significant relationship family history of cancer and pap smear test (p<0.05). In all, prevention is always prior to treatment. One of the prevention ways is the screening test. Early diagnosis and early treatment of cervical cancer has a key role. So the female population needs planning by intervention programs for health education and regular screening to prevent cancer.